ANALISIS KRITIS DEEP LEARNING MELALUI TELAAH MENGENAL DIRI - Nurul Azizah; Selvia Dwi Rahmawati; Yunita Sekarning Tyas; Warni Dwi Astuti; Siti Fathiroh; Wardah Fichayati; Fauzi Annur (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Rapid social, cultural, and technological changes have made reflective thinking and character development essential components of contemporary education, while educational practices continue to emphasize academic achievement over holistic personal growth. This study explores how deep learning and self-awareness are represented in Tara Westover's novel Educated and examines their relevance to character development in contemporary educational contexts. The study employed a library research design using a content analysis approach, with Educated as the primary data source, supported by 26 relevant scholarly publications published within the last five years. The analysis focused on identifying and interpreting representations of mindful learning, meaningful learning, and joyful learning to examine their relationship with the protagonist's identity development. The findings reveal that the educational experiences portrayed in the novel foster reflective awareness, critical thinking, emotional resilience, independence, and the courage to construct an authentic identity. Furthermore, deep learning extends beyond the acquisition of knowledge by enabling individuals to interpret life experiences in ways that contribute to character formation. This study broadens the conceptual understanding of deep learning by demonstrating that literary works can represent reflective learning processes and serve as a conceptual resource for developing more contextual character education that emphasizes the cultivation of self-awareness. ABSTRAK Perkembangan sosial, budaya, dan teknologi menempatkan kemampuan reflektif serta pembentukan karakter sebagai kebutuhan penting dalam pendidikan, sementara praktik pembelajaran masih cenderung menitikberatkan pada pencapaian akademik. Kajian ini mengeksplorasi bagaimana deep learning dan proses mengenal diri direpresentasikan dalam novel Educated karya Tara Westover serta maknanya bagi penguatan karakter di era kontemporer. Analisis dilakukan melalui library research dengan pendekatan analisis isi terhadap novel sebagai sumber utama yang diperkaya oleh 26 publikasi ilmiah relevan terbitan lima tahun terakhir. Proses analisis diarahkan pada identifikasi dan interpretasi representasi mindful learning, meaningful learning, dan joyful learning untuk memahami keterkaitannya dengan perkembangan identitas tokoh utama. Temuan penelitian memperlihatkan bahwa pengalaman pendidikan dalam novel menjadi ruang refleksi yang mendorong berkembangnya kesadaran diri, kemampuan berpikir kritis, ketahanan emosional, kemandirian, serta keberanian membangun identitas secara autentik. Pembelajaran mendalam juga tampak tidak terbatas pada penguasaan pengetahuan, tetapi berkembang menjadi proses memaknai pengalaman hidup yang berkontribusi terhadap pembentukan karakter. Kajian ini memperluas perspektif deep learning dengan menunjukkan bahwa karya sastra dapat merepresentasikan proses pembelajaran reflektif sekaligus menjadi rujukan konseptual bagi pengembangan pendidikan karakter yang lebih kontekstual dan berorientasi pada penguatan self-awareness.